Identifying Disruptive Technologies in IT Industry - Rouhani Zeidanloo, Hossein (2025)
In the dynamic realm of the IT industry, accurately assessing a company’s potential to disrupt or be disrupted is crucial for maintaining a competitive advantage. However, there is currently a lack of a comprehensive methodology that enables the anticipation of disruptive innovation (DI) within this sector. This research addresses this gap by introducing an innovative framework designed to evaluate the disruptive potential of IT companies in relation to one another. Unlike traditional models that primarily focus on predicting disruptive technologies, this framework adopts a multi-dimensional approach to analyze how companies might impact each other through innovation, incorporating factors such as business model innovation, customer demand, network effects and technological advancement. The primary objective of this dissertation is to propose a framework for the timely identification of disruptive innovations, providing a holistic tool that integrates a strong theoretical foundation with practical application. The framework was developed through an extensive review of existing models predicting technological disruptions and was further refined using qualitative research, including in-depth interviews with a diverse range of IT professionals, such as managers, engineers, product managers, CTOs, consultants, and marketing managers. These conversations provided valuable insights into the practical realities of the IT sector, ensuring the framework encompasses a wide range of perspectives across technical, managerial, and strategic dimensions.